A newly developed tetraplex real‐time RT‐PCR for simultaneous screening of influenza virus types A, B, C and D. Issue 1 (22nd October 2018) - Henritzi, Dinah; Hoffmann, Bernd; Wacheck, Silke; Pesch, Stefan; Herrler, Georg; Beer, Martin; Harder, Timm C.
Abstract : Background: Human‐ or avian‐to‐swine transmissions have founded several autonomously circulating influenza A virus (IAV) lineages in swine populations that cause economically important respiratory disease. Little is known on other human influenza virus types, like B (IBV) and C (ICV) in European swine, and of the recently detected novel animal influenza virus type D (IDV). Objectives: Development of a cost‐effective diagnostic tool for large‐scale surveillance programmes targeting all four influenza virus types. Methods: An influenza ABCD tetraplex real‐time RT‐PCR (RT‐qPCR) was developed in the frame of this study. A selection of reference virus strains and more than 4000 porcine samples from a passive IAV surveillance programme in European swine with acute respiratory disease were examined. Results: Two IBV, a single IDV but no ICV infections were identified by tetraplex RT‐qPCR. IBV and IDV results were confirmed by conventional RT‐PCR and partial sequence analysis. Conclusions: The tetraplex RT‐qPCR proved fit for purpose as a sensitive, specific and high‐throughput tool to study influenza virus transmission at the human‐animal interface. Complementing close‐meshed active virological and serological surveillance is required to better understand the true incidence and prevalence of influenza virus type B, C and D infections in swine.